Synchronization and arbitration in digital systems - Kinniment, D. J. (David John) (J. Wiley & Sons, 2007)
Today's networks of processors on and off chip, operating with independent clocks, need effective synchronization of the data passing between them for reliability. When two or more processors request access to a common resource, such as a memory, an arbiter has to decide which request to deal with first. Current developments in integrated circuit processing are leading to an increase in the numbers of independent digital processing elements in a single system. With this comes faster communications, more networks on chip, and the demand for more reliable, more complex, and higher performance sy.